Comparative Immune Responses to Licensed Herpes Zoster Vaccines. (22nd September 2018) - Weinberg, Adriana; Kroehl, Miranda E; Johnson, Michael J; Hammes, Andrew; Reinhold, Dominik; Lang, Nancy; Levin, Myron J
Abstract: Background: Live attenuated (ZV) and recombinant adjuvanted (HZ/su) zoster vaccines differ with respect to efficacy, effect of age, and persistence of protection. We compared cell-mediated immunity (CMI responses to ZV and HZ/su. Methods: This was a randomized, double-blind, placebo-controlled trial stratified by age (50–59 and 70–85 years) and by HZ vaccination status (received ZV ≥5 years before entry or not). Varicella zoster virus (VZV)– and glycoprotein E (gE)–specific CMI were analyzed by interleukin 2 (IL-2) and interferon gamma (IFN-γ) FluoroSpot and flow cytometry at study days 0, 30, 90, and 365. Results: Responses to ZV peaked on day 30 and to HZ/su (administered in 2 doses separated by 60 days) peaked on day 90. Age and vaccination status did not affect peak responses, but higher baseline CMI correlated with higher peak responses. HZ/su generated significantly higher VZV-specific IL-2 + and gE-specific IL-2 +, IFN-γ +, and IL-2 + /IFN-γ + peak and 1-year baseline-adjusted responses compared with ZV. VZV-specific IFN-γ + and IL-2 + /IFN-γ + did not differ between vaccines. HZ/su generated higher memory and effector-memory CD4 + peak responses and ZV generated higher effector CD4 + responses . Conclusions: The higher IL-2 and other memory responses generated by HZ/su compared with ZV may contribute to its superior efficacy. Clinical Trials Registration: NCT02114333.